Republic of Moldova : Staff Report for the 2020 Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report, 2020)
This paper discusses the Republic of Moldova's IMF staff report for Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument. The IMF support will help finance the health and macroeconomic stabilization measures, catalyze donor support, and shore up confidence in Moldova. While downside risks have intensified, public debt remains sustainable with low risk of distress. Beyond the immediate response, the authorities have reinforced their commitment to engage in a governance-focused arrangement with the IMF in the coming months. The IMF stands ready to support Moldova in addressing its immediate and medium-term policy challenges. The authorities' policies aim at mitigating the economic and social impact of the crisis and supporting the recovery, while maintaining macroeconomic and financial stability. They have ramped-up spending to respond to urgent healthcare needs, provided temporary tax relief and subsidized credit schemes to protect employment and businesses, and strengthened social assistance and unemployment programs. The National Bank of Moldova is ensuring orderly exchange rate adjustment and preventing liquidity distress. Financial policies continue to focus on prudent restructuring of banks' credit portfolios subject to maintaining loan classification and provisioning standards.